2018
DOI: 10.1186/s12940-018-0362-5
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of polychlorinated biphenyls: 1. Development and physiology across 3 generations of rats

Abstract: BackgroundPolychlorinated biphenyls (PCBs) are persistent organic environmental contaminants and known endocrine-disrupting chemicals (EDCs). Previous studies demonstrated that developmental exposure to the weakly estrogenic PCB mixture Aroclor 1221 (A1221) in Sprague-Dawley rats altered sexual development, adult reproductive physiology and body weight. The current study tested the hypothesis that prenatal A1221 exposure not only disrupts these endpoints within an exposed individual’s (F1 generation) lifespan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 57 publications
5
26
0
Order By: Relevance
“…Since then, other EDCs, especially bisphenol A [22], tributyltin [29] and phthalates [30] have also been demonstrated to have adverse transgenerational phenotypes. Limited evidence from our lab also showed transgenerational effects of PCBs [7,31,32]. The current study extended prior work substantially by utilizing more realistic exposures to VIN (1 mg/kg in the current study, vs. 50-100 mg/kg in other studies), the inclusion of PCBs, and epigenetic endpoints in F1 and F3 sperm and brain.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Since then, other EDCs, especially bisphenol A [22], tributyltin [29] and phthalates [30] have also been demonstrated to have adverse transgenerational phenotypes. Limited evidence from our lab also showed transgenerational effects of PCBs [7,31,32]. The current study extended prior work substantially by utilizing more realistic exposures to VIN (1 mg/kg in the current study, vs. 50-100 mg/kg in other studies), the inclusion of PCBs, and epigenetic endpoints in F1 and F3 sperm and brain.…”
Section: Discussionsupporting
confidence: 54%
“…These F3 individuals also showed altered anxiety, social, and sexual behavior [4,5], and had changes in gene expression and metabolic activity in specific brain nuclei [5,6]. An endocrine-disrupting mixture of weakly estrogenic polychlorinated biphenyls (PCBs), Aroclor 1221 (A1221), also caused phenotypic changes through the F3 generation [7].…”
Section: Introductionmentioning
confidence: 99%
“…These data fit within a broadening context of multigenerational and transgenerational effects of multiple EDC classes on various endocrine and metabolic tissues [7,[26][27][28][29]. Recently, studies have demonstrated that changes in the expression and methylation of imprinted genes in the brain persist across three generations after BPA exposure in mice [30].…”
Section: Exposures During Sensitive Developmental Windowssupporting
confidence: 58%
“…As reviewed in Ref. , there are data for transgenerational inheritance of diseases/dysfunctions including reproduction, obesity, psychiatric disorders from a variety of environmental stressors including vinclozolin, bisphenol A, atrazine bisphenol A plus phthalates (DEHP and DBP), permethrin plus DEET, methoxychlor, Jet fuel 8, phthalate (DEHP),dioxin, DDT, PCBs, tributyltin, nicotine, alcohol, calorie restriction, high‐fat diets, folate and stress. Mechanisms currently focus on a variety of epigenetic changes including DNA methylation, histone changes and non‐coding RNAs .…”
Section: Transgenerational Inheritancementioning
confidence: 99%